Origins of the Three-Self Patriotic Movement: John Livingston Nevius - Seibel, Caleb (Kansas State University. Dept. of History, 2012)
This is a historical analysis of the missionary methods introduced to China during the nineteenth century by John Livingston Nevius and his work’s influence on the Three-Self Patriotic Movement (TSPM). This study covers the old system of missions and why Nevius sought to change them. It also discusses the three-self idea as implemented by Nevius as a means to strengthen the Church in China. The paper then addresses how the TSPM later used many of the same ideas introduced by Nevius. Finally, this study demonstrates that Chinese Protestants adopted the three-self idea with the goal of reinforcing the church’s position in China while the new communist government hoped the same ideas would hasten the decline of Protestantism in China.
Keywords: Three-Self Patriotic Movement; TSPM; John Livingston Nevius; China; Christianity; missionaries; three-self